Current and future perspectives on management of systemic sclerosis-associated interstitial lung disease. (3rd October 2019) - Distler, Oliver; Volkmann, Elizabeth R.; Hoffmann-Vold, Anna Maria; Maher, Toby M.
ABSTRACT: Introduction : Systemic sclerosis (SSc) is a rare and complex connective tissue disease characterized by fibrosis of the skin and internal organs. Interstitial lung disease (ILD) is a common complication of SSc and the leading cause of SSc-related death. No drugs are licensed for the treatment of SSc-ILD. Areas covered : This review provides an overview of the current treatment of SSc-ILD and a perspective on investigational therapies, focusing on those studied in randomized controlled trials. Expert opinion : There is substantial room for improvement in the treatment of SSc-ILD. Current treatment focuses on immunosuppressant therapies, particularly cyclophosphamide and mycophenolate. Hematopoietic stem cell transplantation has been shown to improve long-term outcomes, but the risk of treatment-related mortality restricts its use to select patients at specialized centers. Modifying the course of disease to improve outcomes remains the goal for new therapies. Several drugs are under investigation as potential therapies for SSc-ILD, providing hope that the limited treatment armamentarium for SSc-ILD will be expanded and improved in the near future. Expert consensus is needed on how to screen for and monitor SSc-ILD and on when to initiate and escalate therapy.